2018
DOI: 10.1097/md.0000000000010244
|View full text |Cite
|
Sign up to set email alerts
|

Decreased postural control in people with moderate hearing loss

Abstract: Balance is a complex process that involves multiple sensory integrations. The auditory, visual, and vestibular systems are the main contributors. Hearing loss or hearing impairment may induce inappropriate postural strategies that could affect balance and therefore increase the risk of falling.The aim of this study was to understand whether hearing loss could influence balance, cervical posture, and muscle activation in the cervical region.Thirteen patients (61 ± 13 years; 161.8 ± 11.0 cm; 70.5 ± 15.9 kg) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
2
27
0
5
Order By: Relevance
“…3B) may reflect reduced boundaries for balance improvement in patients with worse auditory function. This hypothesis is corroborated by studies showing an increase of center of pressure oscillations in people with sensorineural hearing loss 33 and cochlear implant users with the implant turned off. 37 Although previous studies evaluating postural function in otosclerosis failed to show relations between vestibular testing and both pre-and postoperative hearing, 31,32 it could be hypothesized that an increase in intralabyrinthine disruption due to disease progression, as shown by increased sensorineural hearing loss, could subclinically affect peripheral vestibular function in a way that could hamper the possibility of complete balance restoration.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…3B) may reflect reduced boundaries for balance improvement in patients with worse auditory function. This hypothesis is corroborated by studies showing an increase of center of pressure oscillations in people with sensorineural hearing loss 33 and cochlear implant users with the implant turned off. 37 Although previous studies evaluating postural function in otosclerosis failed to show relations between vestibular testing and both pre-and postoperative hearing, 31,32 it could be hypothesized that an increase in intralabyrinthine disruption due to disease progression, as shown by increased sensorineural hearing loss, could subclinically affect peripheral vestibular function in a way that could hamper the possibility of complete balance restoration.…”
Section: Discussionsupporting
confidence: 52%
“…From a physiological standpoint, it could be speculated that the restoration of efficient sound transmission may partially influence postural function, possibly providing subjects with additional information about the surrounding environment to better control body movements; sound may act as a spatial landmark helping integrating other sensory inputs, thus improving overall balance control. 33,34 In this light, it has been proposed that a sound-induced vestibular activation would evoke a vestibulo-postural reflex, influencing balance; 35,36 indeed, previous works highlighted various effects of sound on posture from increased oscillation on the mediolateral (x) plane 35 to reduced sway in the same axis 37 and beneficial effects on anteroposterior (y) oscillations. 38 In our study population, a reduction in postural sway was found in both x and y planes with eyes open as well as closed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually neurosensory and bilateral and refers to the result of a long period of damage to the auditory system, a variety of physiological degenerations, including damage caused by exposure to noise, ototoxic agents and other disorders caused by different medical treatments. 32 33 34 35…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with other studies on the association between HL and balance. 32 38 In a study aiming at understanding whether HL could influence balance, in which 13 patients with moderate HL were assessed, differences were found in HL and increased posturographic measures, especially the sagittal sway, underlining a reduced postural control in people with hearing impairments. Hearing loss may be associated with an increased risk of falls.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the subjects could use these other inputs to recognize their orientation in space, and thus, we cannot completely deny the effect of sensory inputs other than visual and vestibular inputs (e.g., auditory and somatosensory inputs) during the rotatory task. However, previous studies reported that auditory information seems not to affect head postures (Thomas et al, 2018) and that trunk tactile cues did not affect the subjective sensation of rotation (Cheung and Hofer, 2007). Although the effects of these other sensory inputs seem to be low, further studies are required to assess the effects of the other sensory inputs on vertiginous sensation.…”
Section: Limitationsmentioning
confidence: 91%